Sensitivities in Models with Backward Dynamics - Yonghong Chen; Xunxiang Guo (Discrete Dynamics in Nature and Society)
In this paper, we study some properties of economic model with backward dynamics. We mainly introduce the concept of P-sensitivity and P-Li-Yorke sensitivity especially for the multivalued forward dynamics of such models and characterize P-sensitivity and P-Li-Yorke sensitivity of the multivalued forward dynamics in terms of sensitivity and Li-Yorke sensitivity of an induced single-valued dynamics by using the theory of inverse limits. Similarly, we also characterize the sensitivity and Li-Yorke sensitivity of the single-valued backward dynamics of such models in terms of the corresponding sensitivities of an induced single-valued dynamics.